Cell damage and neutrophils promote the infection of Mycoplasma pneumoniae and inflammatory response. (August 2022) - Zhang, Zhikun; Wan, Ruijie; Yuan, Qing; Dou, Haiwei; Tu, Peng; Shi, Dawei; Fu, Xiaoyan; Xin, Deli
Abstract: Mycoplasma pneumoniae (MP) is an important respiratory pathogen of human. The infection of MP can cause direct damage and immune damage in lung, resulting in Mycoplasma pneumoniae pneumonia (MPP). In this study, we aim to investigate the pathogenesis of MPP by detecting the proliferation of MP under conditions of cell damages and neutrophils in vitro . Firstly, we found the supplements of intracellular fluid, protein and RNA derived from intracellular fluid of A549 cells contribute to the survival of MP, thereby promoting the infection of MP. Cell damage can also significantly contribute to the survival of MP without supplements. At the same time, the additions of supplements contribute to apoptosis and the expression of IL-8 and IL-1β. Further, we found live neutrophils show bactericidal activity to MP, and the phagocytosis of MP promotes apoptosis of neutrophils. When co-incubated with MP and A549 cells, the proliferation of MP in the high neutrophils proportion groups were accelerated with functional decline of neutrophils, and the level of extracellular IL-1β showed a time and dose dependent manner to neutrophils. These results suggest that the release of intracellular nutrients by damaged cells and functional decline of neutrophils can promote the infection of MP and play roles in the activation of inflammatory response. Therefore, lung damage and infiltration of neutrophils would be important factors affecting the development of MPP. Highlights: Cell damage can promote the infection of Mycoplasma pneumoniae (MP). Neutrophil show bactericidal activity to MP. Neutrophils participates in the proliferation of MP. Neutrophil associate with the expression of IL1β during the infection of MP.